2009
DOI: 10.1177/004005990904200208
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering RTI Systems That Work

Abstract: Using collaborative teamwork to build unique response-to-intervention (RTI) systems responsive to the needs and strengths within their separate schools and communities, two Montana elementary schools forged a trail for other schools. Each school encountered different obstacles along the way as well as distinctive ways of defining success. How can schools evaluate the "social validity" of a process, and how does this contribute to success? How did the two schools differ in their decisions on how to implement si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Lembke, Garman, Deno, and Stecker (2010), in their discussion about one school's implementation of RTI, described the importance of the inclusion of four elements: staff and administrative buy-in, the use of curriculum based measurement (CBM), the inclusion of evidenced-based teaching practices in both classroom practice and interventions, and the collaboration of staff. The need for commitment, consistency, and collaboration has been shown in other empirical studies (e.g., Mahdavi & Beebe-Frankenberger, 2009). However, these studies were conducted in an American context where changes to the identification procedures have already occurred (Glover & Diperna, 2007), allowing for early intervention with students who are at risk.…”
Section: Rti Implementationmentioning
confidence: 99%
“…Lembke, Garman, Deno, and Stecker (2010), in their discussion about one school's implementation of RTI, described the importance of the inclusion of four elements: staff and administrative buy-in, the use of curriculum based measurement (CBM), the inclusion of evidenced-based teaching practices in both classroom practice and interventions, and the collaboration of staff. The need for commitment, consistency, and collaboration has been shown in other empirical studies (e.g., Mahdavi & Beebe-Frankenberger, 2009). However, these studies were conducted in an American context where changes to the identification procedures have already occurred (Glover & Diperna, 2007), allowing for early intervention with students who are at risk.…”
Section: Rti Implementationmentioning
confidence: 99%
“…The few published studies that have examined CBM practices by non-school psychologists' have relied on limited samples (Clemens et al, 2016;Jenkins et al, 2013). Specifically, Jenkins et al (2013) surveyed 62 schools, Mellard and colleagues (2009) 41 schools, Tackett et al (2009) five schools, and Mahdavi and Beebe-Frankenberger (2009) two schools regarding their CBM use. Additionally, none of these studies surveyed schools from all U.S. demographic areas and all relied on convenience sampling, which significantly impacts the external validity of their findings (Olsen et al, 2013).…”
Section: Curriculum-based Measuresmentioning
confidence: 99%
“…Moreover, educators are more likely to implement interventions or practices in which they have experience, support, and belief in overall effectiveness (Fixsen, Blase, Naoom & Wallace, ). Although RtI implementation research has found that collaboration is important for teacher acceptance, teacher buy‐in can be difficult to gain (Mahdavi & Beebe‐Franenberger, ).…”
Section: Strategies For Generalization From Stokes and Baer () And Acmentioning
confidence: 99%